Attracting attentive academics: Paper, person or place? - Isabel Günther; Melanie Grosse; Stephan Klasen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
We analyze the drivers of presence (size of audience) and participation (number of questions asked) in parallel sessions at a large economics conference, using the annual meeting of the German Economics Association in 2012 as a case study. We find that the location of the presentation is at least as important for the number of academics attending a talk as the combined effect of the person presenting and the paper presented. Being a presenter in a late morning session on the second day of a conference, close to the place where coffee is served, significantly increases the size of the audience. Single-authored papers with long titles as well as those by junior researchers attract significantly fewer attendees. When it comes to asking questions, location becomes less important, but smaller rooms lead to more questions being asked (by women). Younger researchers as well as very senior researchers attract more questions and comments. There are also interesting and sizable gender effects. Women attend research sessions more diligently than men (at any point in time only half of the registered male economists compared to nearly two-thirds of female economists are attending a session), but seem to ask fewer questions than men. Men are less likely to attend presentations on health, education, welfare, and development economics than women. Our findings suggest that strategic scheduling of sessions could ensure better participation at conferences. Moreover, different behaviors of men and women at conferences might contribute to the lack of women in senior scientist positions.
Keywords: A11; B54; 330; economists; conference; preferences; gender differences